Switching to bictegravir/emtricitabine/tenofovir alafenamide from efavirenz/emtricitabine/tenofovir disoproxil in virologically suppressed people with HIV: findings from a non-randomized clinical trial (EBONY study) - Roberta Gagliardini; Marta Camici; Simone Lanini; Rita Bellagamba; Sandrine Ottou; Maria Maddalena Plazzi; Alessandra Vergori; Valentina Mazzotta; Annalisa Mondi; Marisa Fusto; Jessica Paulicelli; Massimo Tempestilli; et al. (International Journal of Infectious Diseases, 2025)
Objectives: No previous studies specifically explored the switch from efavirenz to bictegravir (BIC)-containing three-drug antiretroviral regimens. This study aimed to evaluate the efficacy and safety outcomes of a treatment switch from efavirenz/emtricitabine/tenofovir disoproxil fumarate (EFV/FTC/TDF) given once daily (OD) or on alternate days (ATAD) to BIC/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) in virologically suppressed people with HIV (PWH). Methods: A pilot, single-arm, prospective study was conducted. Results: Overall, 234 PWH were enrolled. 217 of 234 (92.7%, 95% confidence interval [CI], 88.6-95.7%) participants had HIV-RNA <40 cp/ml at 48 weeks. Virological failure occurred in three participants, none with documented resistance, and all resuppressed without antiretroviral therapy change. After 48 weeks, a slight increase in cluster of differentiation (CD)4 cell count was observed from the baseline (+ 59 cells/mmc, 95% CI, 31; 86, P <0.001), but not in CD4/CD8 ratio. A slight increase in creatinine (mean change +0.11 mg/dl, 95% CI 0.10; 0.13, P <0.001) and a decrease in total cholesterol (mean change −8 mg/dl, 95% CI −14; −3, P = 0.001) were also observed. Conclusions: Our data showed that BIC/FTC/TAF demonstrated high virologic and immunologic efficacy and an excellent safety profile.